2010
DOI: 10.1002/jcb.22646
|View full text |Cite
|
Sign up to set email alerts
|

Protection against cellular stress by 25‐hydroxyvitamin D3 in breast epithelial cells

Abstract: 25-Hydroxyvitamin D(3) (25(OH)D(3)) is a prohormone and a major vitamin D metabolite. The discovery of (25(OH)D(3)) 1 alpha-hydroxylase in many vitamin D target organs has yielded an increased interest in defining the role(s) of 25(OH)D(3) in these tissues. The etiology of cancer appears to be complex and multi-factorial. Cellular stress (e.g., DNA damage, hypoxia, oncogene activation) has been identified as one of the key factors responsible for initiating the carcinogenesis process. In this study, we investi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
54
0
1

Year Published

2011
2011
2017
2017

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 83 publications
(59 citation statements)
references
References 50 publications
4
54
0
1
Order By: Relevance
“…S7B). The latter is consistent with recent reports indicating that 25(OH)D 3 can also act as an agonistic vitamin D receptor ligand (35) or through another mechanism (49).…”
Section: (Oh)d 2 Is a Poor Inducer Of Cyp24 Gene Expression Comparesupporting
confidence: 93%
“…S7B). The latter is consistent with recent reports indicating that 25(OH)D 3 can also act as an agonistic vitamin D receptor ligand (35) or through another mechanism (49).…”
Section: (Oh)d 2 Is a Poor Inducer Of Cyp24 Gene Expression Comparesupporting
confidence: 93%
“…The concentrations of other reagents were determined by preliminary experiments in our laboratory and from reports in the literature. Cell proliferation was determined by crystal violet assay as described previously (Peng et al 2010). Biopsy samples were collected from high-risk colon cancer patients during colonoscopy at University of Illinois hospital.…”
Section: Cell Culture Cell Proliferation and Biopsy Samplesmentioning
confidence: 99%
“…Additionally, it was observed that the inhibition of miR-32 function by the administration of an RNA molecule that is complementary to miR-32 is able to increase the efficiency of cytotoxic therapy [40]. In a similar way, treatment with vitamin D was found to reverse the increase in cell death and in the expression of miR-182 in normal breast cells subjected to stress by growing in low-serum medium culture [41]. Another effect of vitamin D administration is the attenuation of proliferation of human prostate cancer cells when co-administered with testosterone; this treatment produced the upregulation of expression of miR-21, -22, -29a, -29b, -134, -371-5p, and -1207-5p and the downregulation of miR-17, -18, and -20a, that are part of the miR-17/92 cluster [42].…”
Section: Effect Of Macro- and Micronutrients On Mirna Expressionmentioning
confidence: 91%